Bioengineering of fibroblast‐conditioned polycaprolactone/gelatin electrospun scaffold for skin tissue engineering. Issue 6 (27th January 2022) - Yazdanpanah, Ayna; Madjd, Zahra; Pezeshki‐Modaress, Mohamad; Khosrowpour, Zahra; Farshi, Paniz; Eini, Leila; Kiani, Jafar; Seifi, Morteza; Kundu, Subhas C.; Ghods, Roya; Gholipourmalekabadi, Mazaher
Abstract: Background: Synthetic tissue engineering scaffolds has poor biocompatiblity with very low angiogenic properties. Conditioning the scaffolds with functional groups, coating with biological components, especially extracellular matrix (ECM), is an excellent strategy for improving their biomechanical and biological properties. Methods: In the current study, a composite of polycaprolactone and gelatin (PCL/Gel) was electrospun in the ratio of 70/30 and surface modified with 1% gelatin‐coating (G‐PCL/Gel) or plasma treatment (P‐PCL/Gel). The surface modification was determined by SEM and ATR‐FTIR spectroscopy, respectively. The scaffolds were cultured with fibroblast 3T3, then decellularized during freeze‐thawing process to fabricate a fibroblast ECM‐conditioned PCL/Gel scaffold (FC‐PCL/Gel). The swelling and degaradtion as well as in vitro and in vivo biocompatibility and angiogenic properties of the scaffolds were evaluated. Results: The structure of the surface‐modified G‐PCL/Gel and P‐PCL/Gel were unique and not changed compared with the PCL/Gel scaffolds. ATR‐FTIR analysis admitted the formation of oxygen‐containing groups, hydroxyl and carboxyl, on the surface of the P‐PCL/Gel scaffold. The SEM micrographs and DAPI staining confirmed the cell attachment and the ECM deposition on the platform and successful removal of the cells after decellularization. P‐PCL/Gel showed better cell attachment, ECM secretion and deposition after decellularization compared with G‐PCL/Gel. The FC‐PCL/Gel was considered as an optimized scaffold for further assays in this study. The FC‐PCL/Gel showed increased hydrophilic behavior and cytobiocompatibility compared with P‐PCL/Gel. The ECM on the FC‐PCL/Gel scaffold showed a gradual degradation during 30 days of degradation time, as a small amount of ECM remained over the FC‐PCL/Gel scaffold at day 30. The FC‐PCL/Gel showed significant biocompatibility and improved angiogenic property compared with P‐PCL/Gel when subcutaneously implanted in a mouse animal model for 7 and 28 days. Conclusions: Our findings suggest FC‐PCL/Gel as an excellent biomimetic construct with high angiogenic properties. This bioengineered construct can serve as a possible application in our future pre‐clinical and clinical studies for skin regeneration. Abstract : This study presents a cell‐secreted ECM‐conditioned PCL electrospun scaffolds with improved biomechanical and biological properties for bioengineering of skin wound dressing. The scaffold is modified by coating or plasma treatment, and the cells are cultured on the scaffolds. Finally, the cells/scaffold constructs are decellularized by an optimized decellularization with complete removal of the cells and minimal elimination of the secreted ECM. The ECM‐conditioned PCL mat shows improved hydrophilic properties with enhanced biocompatibility and angiogenic properties in vitro and in vivo.